New species of the snakefly genus Inocellia Schneider, 1843 (Raphidioptera: Inocelliidae) from Yunnan, China - Liu, Xingyue; Aspöck, Horst; Zhang, Weiwei; Aspöck, Ulrike (Zootaxa, 2012)
Two new species of the snakefly genus Inocellia Schneider, 1843 from Yunnan Province of China are described: Inocellia nigrasp. nov. and Inocellia yunnanica sp. nov. A revised key is provided for the males of all Inocellia species. The biogeographical significance of the Yunnanian refugial centre is discussed.